Who Voted for Brexit? A Comprehensive District-Level Analysis - Sascha O. Becker; Thiemo Fetzer; Dennis Novy (Center for Economic Studies and ifo Institute (CESifo), 2017)
On 23 June 2016, the British electorate voted to leave the European Union. We analyze vote and turnout shares across 380 local authority areas in the United Kingdom. We find that exposure to the EU in terms of immigration and trade provides relatively little explanatory power for the referendum vote. Instead, we find that fundamental characteristics of the voting population were key drivers of the Vote Leave share, in particular their education profiles, their historical dependence on manufacturing employment as well as low income and high unemployment. At the much finer level of wards within cities, we find that areas with deprivation in terms of education, income and employment were more likely to vote Leave. Our results indicate that a higher turnout of younger voters, who were more likely to vote Remain, would not have overturned the referendum result.
Keywords: D72; N44; R23; Z13; 330; political economy; voting; referendum; migration; austerity; globalisation; UK; Scotland; EU